Skin abnormality and hairloss: the reproductive endocrinological viewpoint (Medical Journal of Indonesia, 2004)
Excessive androgen production may cause changes in female skin, such as hirsutism and acne. The administration of antiadrogenic hormone such as cyproteron acetate, may eliminate the hyperandrogenic effect on the skin. Hairloss may also caused either by hyper-androgenemia or by low estrogen level. The administration of either antiandrogen or estrogen may reduce hairloss. Virilization, which includes excessive growth of hair and clitoris enlargement, deepened voice, muscle hypertrophy and mammary hypoplasia are also associated with hyperandrogenemia. Antiandrogen treatment could eliminate these impacts of virilization. In contrast, cellulite was supected to be due to androgen deficiency, and the use of topical testosterone could eliminate it. It is concluded that skin and/or hairloss are associated with hormonal changes in women. The treatment with antiandrogenic hormones may reduce or cure these abnormalities. (Med J Indones 2004; 13: 258-63)Keywords: Hirsutism, virilization, acne, cellulite, hairloss, androgen, estrogen